ANALISIS PENGARUH AUGMENTED REALITY TERHADAP CUSTOMER EXPERIENCE: STUDI PADA FITUR VIRTUAL TRY-ON DI WEBSITE MAKE OVER INDONESIA - Nurintan, Cherilda Luqia; Wulan Tresna, Pratami; Rivani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid growth of e-commerce has encouraged cosmetic companies to adopt innovative technologies to enhance Customer Experience in online shopping. One of these technologies is Augmented Reality (AR) through the Virtual Try-On feature, which enables consumers to virtually try cosmetic products before making a purchase. This study aims to analyze the effect of Augmented Reality on Customer Experience among users of the Virtual Try-On feature on the Make Over Indonesia website. This research employed a quantitative approach with descriptive and causal methods. Data were collected through questionnaires distributed to 170 female Generation Z respondents who had previously used the Virtual Try-On feature on the Make Over Indonesia website. Data analysis was conducted using validity and reliability tests, classical assumption tests, simple linear regression, t-test, and coefficient of determination analysis with the assistance of SPSS software. The results indicate that the Augmented Reality variable achieved a score of 82.64%, categorized as very high, while Customer Experience scored 81.94%, also categorized as very high. Hypothesis testing revealed that Augmented Reality has a positive and significant effect on Customer Experience, with a t-value of 12.720 and a significance level of 0.000. The coefficient of determination (R²) value of 0.490 indicates that Augmented Reality contributes 49% to Customer Experience, while the remaining 51% is influenced by other fActors beyond the scope of this study. These findings demonstrate that the Virtual Try-On feature effectively enhances Customer Experience by providing a more interActive, informative, and engaging online shopping experience.